Pengaruh Profitabilitas, Likuiditas dan Ukuran Perusahaan terhadap Kebijakan Dividen - Yesi Belina Oktaviana, Shanti; Ali, Hapzi; Yayuk Priyati, Rini (Green Publisher, 2023)
The Influence of Profitability, Liquidity, and Company Size on Dividend Policy is a scientific article of literature study within the scope of the field of financial management. This article aims to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley, and other academic online media. The library research method comes from e-books and open-access e-journals. The results of this article: 1) Profitability affects Dividend Policy; 2) Liquidity affects Dividend Policy; and 3) Company Size affects Dividend Policy. Other factors that influence dividend policy include leverage, company growth, institutional ownership, and managerial ownership.